ASUPAN KARBOHIDRAT DAN PROTEIN BERHUBUNGAN DENGAN STATUS GIZI ANAK SEKOLAH DI SYAFANA ISLAMIC SCHOOL PRIMARY, TANGERANG SELATAN TAHUN 2017 - Mutia Sari Parinduri; Debby Endayani Safitri (UHAMKA PRESS, 2018)
Nutritional status in elementary student has influenced by the amount of nutrient intake. Many factors are influencing the nutritional status which were direct factors (nutrient intake and infectious diseases) and indirect factors (food safety, childcare patterns, healthy environment, and access to health services). This study aimed to determine the relationship between the consumption of fast food, calorie beverages, and nutrient intake with nutritional status of elementary student in Syafana Islamic School Primary conducted in October-November 2017. The study design was a cross-sectional with 175 subjects. Places and subjects were selected with proportional random sampling. Data were collected through anthropometric measurements, FFQ, recall 2 x 24 hours, and self-administered questionnaire. Questionnaires were given to subjects to know of characteristics student (gender and pocket money), fast food consumption, calorie beverages, and nutrient intake (energy and macronutrients), and nutritional status. Data were tested using statistical test chi-square. The result of the chi-square statistic test showed that was relation between carbohydrate intake (p<0.05) and protein intake (p<0.05) with nutritional status. There was no relationship between fast food consumption, calorie beverages (p>0.05), energy intake (p>0.05), and fat intake (p>0.05) with nutritional status.